Unveiling plant cell signaling: cell death responses and AtRGS1 phospho-barcode - Simoni, Eduardo Bassi (2024)
Plant adaptation/acclimatation relies on the perfect adjustment of the organism and the environment interaction, requiring a complex and robust cooperation among different players. Any alteration in this interaction can disrupt the cell homeostasis, activating various responses. From signal perception to gene expression regulation and subsequently cell fate control, intricate signaling cascades play essential roles in these processes, facilitating communication among diverse organelles. In the present work, we aimed to describe and seek elucidating factors that are involved in specific cell signaling, as well as their function in the perception, propagation, and the response to an environmental signal. Firstly, in the first chapter titled “Cell death signaling from endoplasmic reticulum stress: plant-specific and conserved features'', we reviewed the main aspects of the endoplasmic reticulum (ER) stress signaling and its evolutionary conservation in plant organisms, focusing on the different cell death signaling activated by ER stress responses. The ER is an important organelle responsible for controlling the correct folding and post-translational modification of secretory proteins, Ca2+ homeostasis and protein quality control. Under normal conditions the ER protein dynamic is stabilized by the rate of synthesis/folding and organelle loading system. However, when the correct balance is disrupted, it starts accumulating unfolded proteins and, thus, triggers signaling pathways to restore the normal condition, such as the unfolded protein response (UPR). The unfolded protein accumulation can be triggered by many different conditions, such as biotic and abiotic stresses. To restore the perfect balance in the ER four main processes are stimulated: decreasing the protein synthesis rate; an increase in the ER chaperone expression; positive modulation of ERAD genes; expansion of ER internal capacity. Those mechanisms can be modulated by two main branches that are associated with ER-membrane- bound proteins: IRE1 and bZIP transfactors. The molecular chaperone BiP, also plays an important role in the signaling modulation, acting as chaperone and sensor of the stress. Thus, the combination of different factors and responses allow the cell to cope with ER stress in order to maintain the cell function and survival. However, prolonged stress conditions that cannot be restored may trigger autophagy or programmed cell death (PCD) responses originating from the ER, enabling organism survival at the expense of specific cells. Plant PCD shares conserved and unique signaling pathways capable of modulating, activating, and executing the cell death process. A unique plant response involves NAC (NAN/ATAF/CUC) transcription factor family modules, which can include: the DCD/NRP-mediated cell death component; bZIP28/bZIP60- ANAC089-mediated cell death component; ANAC013/ANAC017 component. Collectively, these diverse mechanisms are important in cell homeostasis, by perceiving, propagating, and activating specific responses in order to maintain the organism's survival. Likewise, another conserved signaling pathway was studied in Chapter 2 titled “Revealing the impact of AtRGS1 residues phosphorylation in the plant cell signaling”. In this chapter we seek to understand the effect of post-translational modifications on RGS1, and their role on the structure and function of AtRGS1. Heterotrimeric G-proteins, vital for growth, development, stress responses, and pathogen defense, are negatively regulated by the seven-transmembrane Regulator of G-protein signaling (7TM-RGS) instead of GPCRs found in animals. Arabidopsis AtRGS1, with its C-terminus serine phosphorylation cluster, detaches from the G- protein alpha subunit (AtGPA1) upon phosphorylation, activating beta-arrestin-like endocytosis and G-signaling cascades. Beyond the cluster, AtRGS1 has serine residues at the RGSbox terminus (Ser417) and linker region (Ser278), often overlooked due to the focus on truncated forms. Our molecular dynamics simulations (MDS) on a plant plasma membrane model show that phosphorylation in the linker region controls RGS domain positioning via hydrogen bonds with RGSbox residues. This mechanism, consistent in the phospho-mutant S278E, is also seen in lycophytes, suggesting a conserved regulatory pattern. In vivo Split Firefly Luciferase (SFluc) assays revealed that the S278E variant, mimicking phosphorylated S278, exhibits reduced interaction with AtGPA1 compared to wild type. Additional MDS and SFluc analysis with several phosphomimetic mutants of both proteins indicated that concurrent phosphorylation of S278 in AtRGS1 and Y166 in AtGPA1 is necessary for stable interaction, pointing to a complex interplay of phosphorylation events in plant G protein regulation. Our findings also demonstrate that phosphorylation of S278 is a pivotal modulator in the internalization, stability and nuclei translocation processes. Finally, S278 residue has an important role in the anti-bacterial immune system response. Collectively, these results suggest that the phosphorylation pattern of AtRGS1, especially S278 and cluster, acts as a barcode directing responses to various elicitors, influencing membrane domain positioning and overall signaling processes. Keywords: UPR; ER-stress; Programmed cell-death; RGS1; G-signaling; Phosphorylation; Structure; Internalization.